Weldability Studies of Novel Chromium Free Electrodes with Austenitic Grade Stainless Steels - Koushik Kosanam; J. R. Nataraj (New Approaches in Engineering Research Vol. 2, 2021)
Stainless Steels are widely used materials due to their high corrosion resistance and good mechanical properties. However, welding of Stainless Steel produces hexavalent chromium fumes which are carcinogenic to the welders and operators in the vicinity of the welding. As per Occupational Safety and Health Administration suggestions, a novel filler material has been developed to mitigate these hexavalent fumes. The main aim of this chapter is to discuss development of chromium free filler material for welding of austenitic grade Stainless steel and investigate mechanical and corrosion resistance of the weldments. This case study includes development of filler material, microstructure characterization, analyzing effect of welding parameters like Current, Gas Flow Rate and Root Gap on properties of weldment like Ultimate Tensile strength, Impact Strength, Hardness and Corrosion Resistance, and optimization of welding parameters by Taguchi and Response Surface Methodology (RSM). The weldments have shown the maximum Tensile strength of 324 MPa, maximum Hardness of 209VHN, and a minimum corrosion rate of 1.575e-004mils/year for an optimum current value of 130A, 11.79litres/min gas flow rate, and 2.33mm root gap.